Wetland management of Kuala Selangor Nature Park, Malaysia - Asmawi, M. Zainora; Abdul Aziz, Zainul Ariffin; Abdulaziz, Hassan (KAED, IIUM, 2009)
Malaysia is a country blessed with wetlands of various sizes, types and functions. They are economically, socially, culturally and recreationally significant. Wetlands management in Malaysia has advanced from the traditional approach to modern one with strong support of governmental and nongovernmental organisations, legislation, and sophisticated technologies. Wetland is associated with values; among them are hydrological functions such as flood protection, maintenance of stream flow, recharging ground water. It serves as recreational area, habitats for both flora and fauna, and also promotes educational and research grounds. The study area, i.e. Kuala Selangor Nature Park is among the wetlands of significant role. Questionnaire survey was conducted on 100 respondents, asking their opinion on the aspect of wetland management of the site. Study indicated that relatively local visitors acknowledged the importance of wetland though they felt that government should enforce relevant legislation pertaining to wetland more seriously. Moreover, respondents thought that legislation can be used as a means to manage wetlands. In addition, there is a need to sustain the natural environment due to its combined effects as well as its relevancy towards sustaining the natural setting, so that man will continue enjoying the beautiful contributions of the natural environment.